Interregional stunting prevalence determinants from a regional perspective in Indonesia: multivariate and spatial analysis approaches - Kikin Windhani; Fajar Hardoyono; Ratna Setyawati Gunawan; Dicky Satria Ramadhan; Anzar Alfat Firdaus (Intelektual Pustaka Media Utama, 2026)
Stunting continues to be a significant public health issue globally, impacting millions of children and hindering long-term human capital development. Prior studies on stunting have predominantly focused on individual factors, neglecting the influence of regional characteristics. The majority of analyses depend on global regression models that presume consistent correlations across areas inclined to using many variables. This research applied Geographically Weighted Spatial Regression to analyze stunting risk factors across 514 districts in Indonesia. By identifying spatially variable determinants, this study supports more targeted and effective stunting reduction strategies. The research results using geographic information systems (GIS) and multivariate analysis show that stunting is highest in eastern Indonesia, where poor sanitation is the dominant factor causing stunting. The policy implemented by the local government is to enhance collaboration with various parties, including academics, government, private sector, and communities, in addressing stunting.